Características de Sedimentos Obtidos em Perfurações na Restinga de Jacarepaguá - RJ - Marques, Jorge Soares (Anuário do Instituto de Geociências, 1985)
The granulometric analysis results of sand sediments obtained through two boring in the Jacarepaguá beach ridge are shown. This paper presents the differences among two sample colections of sand and some observations about the lagunar and marine process correlated with these sediments.